Pengukuran Kemampuan Memahami Teks Narasi Siswa Kelas X SMK As-Shofa Melalui Taksonomi Barrett - Neneng Hartini; Asep Nurjamin (Yayasan Al-Afif, 2026)
This study aims to describe the reading comprehension ability of tenth-grade students at SMK As-Shofa in understanding narrative texts based on Barrett’s Taxonomy. The research employed a quantitative approach with a descriptive research design. The population consisted of 321 students, while the sample was 24 students from class X Pharmacy A selected through purposive sampling. Data were collected using a reading comprehension test developed according to the five levels of Barrett’s Taxonomy: literal, reorganization, inferential, evaluation, and appreciation. The instrument was validated by Indonesian language teachers to ensure content validity. Data analysis was conducted using descriptive quantitative techniques, including scoring, percentage calculation, and categorization. The results showed that students’ reading comprehension ability was generally in the sufficient to very good category. Most students demonstrated strong performance at the literal and reorganization levels, indicating good ability to identify explicit information and organize text structure. However, their performance at the inferential, evaluative, and appreciative levels was relatively lower, suggesting limitations in critical and reflective reading skills. The distribution of scores revealed that 70.83% of students were in the sufficient category, 20.83% in the good category, and 8.33% in the very good category. These findings indicate that although basic comprehension skills are well developed, higher-order thinking skills in reading still require improvement. The application of Barrett’s Taxonomy proved effective in systematically mapping students’ reading abilities and can serve as a useful reference for improving reading instruction and assessment. Kata kunci: reading comprehension, narrative text, Barrett’s Taxonomy, quantitative descriptive study, secondary school students